The Choice of Technology and Export Commitment: The Peruvian Textile Industry - Daniels, John D.; Robles, Fernando (Journal of International Business Studies, 1982)
The purpose of this study was to examine the relationship between the adoption of capital-intensive technologies and export commitment of Peruvian textile firms. The results suggested a positive relationship. One possible reason is that exporters must be more concerned with product quality perceptions and delivery reliability which may be higher through the use of labor-saving innovations. Another is that lower production costs may be more important in external markets which are more competitive. The study elaborates on the complex factors affecting technology choice, emphasizing that there are country, industry, product, and innovation specific variables which affect the use of so-called appropriate technology.